2008
DOI: 10.1002/anie.200702505
|View full text |Cite
|
Sign up to set email alerts
|

Nanomaterials for Rechargeable Lithium Batteries

Abstract: Energy storage is more important today than at any time in human history. Future generations of rechargeable lithium batteries are required to power portable electronic devices (cellphones, laptop computers etc.), store electricity from renewable sources, and as a vital component in new hybrid electric vehicles. To achieve the increase in energy and power density essential to meet the future challenges of energy storage, new materials chemistry, and especially new nanomaterials chemistry, is essential. We must… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

27
3,857
1
11

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 5,651 publications
(3,946 citation statements)
references
References 103 publications
27
3,857
1
11
Order By: Relevance
“…The estimated energy density of lithium ion batteries based on Li 4 Ti 5 O 12 anode (regarding both potential and capacity) does not exceed one third of that on graphite if they are coupled with a typical 4 V cathode. 5 It was recently reported that Li can be intercalated into the layered transition metal oxide LiVO 2 , 6 but its major difficulty for application as an anode lies in the fast 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 deterioration of the material.…”
mentioning
confidence: 97%
See 3 more Smart Citations
“…The estimated energy density of lithium ion batteries based on Li 4 Ti 5 O 12 anode (regarding both potential and capacity) does not exceed one third of that on graphite if they are coupled with a typical 4 V cathode. 5 It was recently reported that Li can be intercalated into the layered transition metal oxide LiVO 2 , 6 but its major difficulty for application as an anode lies in the fast 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 deterioration of the material.…”
mentioning
confidence: 97%
“…Furthermore, the thick solid electrolyte interphase (SEI) layer on its surface could also introduce kinetic problems for fast charge and discharge. 8 Li 4 Ti 5 O 12 has been found to change its structure negligibly during the discharge/charge process, and possesses good lithium ion mobility and a long and stable voltage plateau, together with low cost, environmental friendliness, and enhanced safety. [8][9][10] Nevertheless, its potential is still relatively higher, about 1.6 V (versus Li + /Li), thus halving the overall cell voltage and negating the benefits.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…
Significant effort has been devoted by research groups world-wide to the development of polymer and composite polymer electrolytes for use in lithium batteries [1,2] . The best known polymer ionic conductor, polyethylene oxide (PEO), is crystalline and has low conductivity at room temperature.
…”
mentioning
confidence: 99%